ANALYSIS OF A REHABILITATION PROGRAM IN HOSPITALIZED PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE (Fiep Bulletin - online, 2016)
The chronic obstructive pulmonary disease is a disease that causes more damage and that kills the world, reach about 5% of the population and is more common among men and after 40 years, bringing major functional impairment to patients. This is characterized by chronic airway, airway inflammation, limiting airflow and that not is fully reversible and may be more possible prevention and treatment. This study is characterized by a clinical trial uncontrolled, with a transverse design, aiming to assess whether anaerobic exercises of upper limb and lower limb and exercise on a cycle ergometer generates a change in the FIM scale in patients with COPD hospitalized at São Lucas/FAG Hospital. Six patients with COPD were studied, and found that despite the improvement in the values ??of the FIM this was not statistically significant. We conclude  the proposed protocol showed no hemodynamic change significant, nor in the variables of FIM.
Keywords: COPD; Independence; Functional; Physical Exercise.